Hubungan Antara Obat Yang Digunakan Terhadap Kejadian Kausalitas Adverse Drug Reactions (ADRs) dengan Menggunakan Skala WHO UMC Pada Pasien Congestive Heart Failure - Annis Rahmawaty; Rifda Naufa Lina; Gunawan Firmansyah (LPPM Universitas Abdurrab, 2026)
Patients with Congestive Heart Failure (CHF) are often prescribed combination therapy, which may lead to Adverse Drug Reactions (ADRs). ADRs assessment can be performed using the WHO-UMC scale by considering the clinical pharmacological aspects of the case history, as well as the quality of documentation and patient observation. This study aimed to determine the relationship between the number of drugs used and the causality of ADRs based on the WHO-UMC scale in patients with Congestive Heart Failure. Data were collected prospectively during June 2025 from 58 patients with a duration of CHF of more than one year at RSI Sunan Kudus. The sampling technique used was total sampling. Data were analyzed descriptively using an observational approach, while the correlation analysis was conducted using the Chi-square test and Fisher’s Exact Test. The results showed that the majority of patients were aged 45–59 years, accounting for 29 patients (50%). ADRs were more frequently observed in male patients, with 36 cases (62.1%), compared to female patients, with 22 cases (37.9%). there are 49 comorbid diseases in patients. The most frequently reported ADR was dizziness, occurring in 17 cases (24.6%), while the most common causality category based on the WHO-UMC scale was “possible,” found in 36 cases. Most patients received more than five medications, with 44 cases reported. In conclusion, there was a significant relationship between the number of medications used and the causality of ADRs based on the WHO-UMC scale in patients with Congestive Heart Failure. The greater the number of medications administered, the higher the risk of ADRs.